2011
DOI: 10.3892/or.2011.1282
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable clinical implications for hypermethylation of RUNX3 in patients with salivary gland adenoid cystic carcinoma

Abstract: Abstract. to elucidate the potential etiological role of rUnX3 in the development of salivary gland adenoid cystic carcinoma (Acc), we analyzed the methylation status of rUnX3 in a series of 114 Acc tissues and 3 Acc cell lines. results showed that the methylated rate of rUnX3 was 50.9 and 3.5% in the 114 Acc samples and the corresponding normal salivary glands, respectively, achieving a significant difference (p<0.001).There was a significant correlation between RUNX3 methylation and various clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Human Runt-related transcription factor 3 (RUNX3) is a negative regulatory gene of malignant tumors whose abnormal expression is closely related to various human malignant tumors. For example, RUNX3 expression has been reported to be down-regulated in gastric cancer, 19 liver cancer, 20 breast cancer, 21 adenoid cystic carcinoma [22][23][24] and other tumor tissues, and indicated poor prognosis. Prior in vitro experiments showed that overexpression of RUNX3 could induce tumor cell apoptosis while inhibiting proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Human Runt-related transcription factor 3 (RUNX3) is a negative regulatory gene of malignant tumors whose abnormal expression is closely related to various human malignant tumors. For example, RUNX3 expression has been reported to be down-regulated in gastric cancer, 19 liver cancer, 20 breast cancer, 21 adenoid cystic carcinoma [22][23][24] and other tumor tissues, and indicated poor prognosis. Prior in vitro experiments showed that overexpression of RUNX3 could induce tumor cell apoptosis while inhibiting proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%